The Cys-Arg/N-end rule pathway is a general sensor of abiotic stress in flowering plants - Vicente, Jorge; Mendiondo, Guillermina M.; Movahedi, Mahsa; Peirats-Llobet, Marta; Juan, Yu-ting; Shen, Yu-yen; Dambire, Charlene; Smart, Katherine; Rodriguez, Pedro L.; Charng, Yee-yung; Gray, Julie E.; Holdsworth, Michael J. (Elsevier (Cell Press), 2017)
Abiotic stresses impact negatively on plant growth, profoundly affecting yield and quality of crops. Although much is known about plant responses, very little is understood at the molecular level about the initial sensing of environmental stress. In plants, hypoxia (low oxygen, which occurs during flooding) is directly sensed by the Cys-Arg/N-end rule pathway of ubiquitin-mediated proteolysis, through oxygen-dependent degradation of group VII Ethylene Response Factor transcription factors (ERFVIIs) via amino-terminal (Nt-) cysteine [1, 2]. Using Arabidopsis (Arabidopsis thaliana) and barley (Hordeum vulgare), we show that the pathway regulates plant responses to multiple abiotic stresses. In Arabidopsis, genetic analyses revealed that response to these stresses is controlled by N-end rule regulation of ERFVII function. Oxygen sensing via the Cys-Arg/N-end rule in higher eukaryotes is linked through a single mechanism to nitric oxide (NO) sensing [3, 4]. In plants, the major mechanism of NO synthesis is via NITRATE REDUCTASE (NR), an enzyme of nitrogen assimilation [5]. Here, we identify a negative relationship between NR activity and NO levels and stabilization of an artificial Nt-Cys substrate and ERFVII function in response to environmental changes. Furthermore, we show that ERFVIIs enhance abiotic stress responses via physical and genetic interactions with the chromatin-remodeling ATPase BRAHMA. We propose that plants sense multiple abiotic stresses through the Cys-Arg/N-end rule pathway either directly (via oxygen sensing) or indirectly (via NO sensing downstream of NR activity). This single mechanism can therefore integrate environment and response to enhance plant survival.